Childhood tonsillectomy alters the primary distribution of HPV‐related oropharyngeal squamous cell carcinoma. Issue 2 (11th February 2020) - Altenhofen, Brannon; DeWees, Todd A.; Ahn, Ji W.; Yeat, Nai C.; Goddu, Shreya; Chen, Ishita; Lewis, James S.; Thorstad, Wade L.; Chole, Richard A.; Gay, Hiram A.
Abstract: Objectives: We investigated how tonsillectomy during childhood may influence the distribution of human papillomavirus (HPV) positive cancer of the tonsils in adult life using p16 as a surrogate marker for HPV infection. Study Design: Retrospective observational study. Methods: A total of 280 patients diagnosed with oropharyngeal squamous cell carcinoma (OPSCC) and known p16 status were eligible for this study. Each participant was called to obtain the childhood tonsillectomy history. Respondents were subgrouped by p16 status and the primary tumor location. Patient demographic and clinical information was analyzed for association with Fisher's exact and Wilcoxon rank sum tests. Location of tumor was modeled using univariate (UVA) and multivariate (MVA) logistic regression with associated odds ratios (OR) and 95% confidence intervals. Results: Of the 280 patients, 115 (41%) were respondents: 104 (90.4%) were p16 positive and 11 (9.6%) were p16 negative. For p16 positive patients, we observed a majority (93%) of intact tonsils in those with tonsil cancer, compared to 45% of intact tonsils in patients with p16 positive cancer elsewhere in the oropharynx ( P  < .001). MVA logistic regression showed that female gender (OR = 4.16, P = .0675), prior smoking history (OR = 2.6, P = .0367), and intact tonsils (OR = 15.2, P  < .0001) were associated with tonsillar OPSCC. Conclusion: We found that patients with p16 positive OPSCC at a non‐tonsil site were much more likely to have had prior tonsillectomy vs those with p16 positive OPSCC arising within the tonsil. Nevertheless, we do not advocate tonsillectomies as a public health policy to reduce HPV‐related OPSCC. Level of Evidence: 6